Integration of a bidirectional cell in a quasi-Z-source inverter for CMV reduction and pure sinusoidal wave form - Mohammad Imron Dwi Prasetyo; Muhammad Syahril Mubarok; Sofyan Muhammad Ilman; Misbahul Munir; Nur Vidia Laksmi B (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
With the increasing global commitment to renewable energy sources like photovoltaics (PV), there is a critical need for high-efficiency and high-power-quality converter topologies. Traditional two-stage PV systems are often complex and introduce significant Common Mode Voltage (CMV), leading to issues like leakage currents, high electromagnetic interference, and safety concerns. This paper proposes the Integration of a Bidirectional Cell within a quasi-Z-Source Inverter (BC-qZSI) to achieve CMV Reduction in a single-stage power conversion setup. The BC acts as an active balancing and filtering element rather than solely a boosting stage, ensuring a continuous current mode and actively suppressing the high-frequency CMV components generated by the shoot-through states. The analytical mathematical expression of the proposed topology is derived to confirm its operation, voltage boost capability, and CMV characteristics. Ideal simulation results, performed using PSIM software, validate the derived expressions and demonstrate the effectiveness of the proposed design. The topology achieves a significant reduction in CMV, lowering its amplitude more than 90% compared to the conventional qZSI. Furthermore, the output waveform quality is excellent, yielding a Total Harmonic Distortion (THDv) of 2 %, which complies with the IEEE Std 519-2014 standard for acceptable waveform quality. These results confirm that the integrated BC-qZSI topology effectively mitigates CMV while maintaining high power quality and a single-stage architecture.